Penerapan Media Tumpeng Gizi Seimbang Terhadap Pengetahuan Gizi Siswa Kelas 5 - 6 di SDN 11/262 Semolowaru - Ferdiana, Suci; Nasir, Muhammad (Infokes, 2017)
For slather  arise problem nutrition the, need socialized guidelines nutrition balanced that can made as guidelines eat, move physical, life clean and maintain weight body normal.Research this is type research quasy experiment. Research quasy experiment.Technique total sampling, that is technique taking sample that do with teke whole population as sample for investigated that is as much 74 students. Instrument that in use that is test knowledge/questionnaire and sheet behind.Level knowledge nutrition students besed on design counseling thet use media show that in part big students have knowledge nutrition less that is as much 7 (18,4%) students that have knowledge nutrition that enough as much 25 (65,7%) person and have knowledge good as much 6 (15%) students. As for level knowledge nutrition students based on counseling no use media show that as much 18 (24,3%) students that have knowledge that less as much 15 (20,3%) students, and have knowledge good as much 3 (4%) students. Results analysis statistics use test T  obtained value p=0,017 and a=0,005 by because p<a then H0 rejected that that is there is difference between application media tumpeng nutrition sheet behind with no use sheet behind  Based on results test T statistics show that no use sheet behind more nice of the that use sheet behind. For agency health need geve socialization to students schoolgirl in SD because still many child SD not yet knowledge tumpeng nutrition or four pillar nutrition balanced.